COMPROMISE SOLUTION TO THE CONFLICTING OBJECTIVES IN THE MANAGEMENT OF THE ARAFURA SEA SHRIMP FISHERY - Purwanto Purwanto (Research Center for Fisheries, 2011)
Fisheries mis-management, including over allocation of fishing vessels, and illegal fishing practices in the Arafura Sea shrimp fishery had resulted in over exploitation of shrimp stock and economic losses.